1979
DOI: 10.1055/s-0028-1092799
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Function in Patients with Spinal Cord Damage

Abstract: Vaying degrees of testicular dysfunction are found in men with traumatic spinal cord damage. Eighteen paraplegic men have been studied and the gonadotropin response to luteinizing hormone-releasing hormone (LRH) measured. Basal serum testosterone estimations were made and in eight of the patients testicular testosterone reserve was assessed by the testosterone response to human chorionic gonadotropin (HCG). Testicular biopsies were performed in seven cases. In three of these patients, the testicular biopsies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 1 publication
1
11
0
2
Order By: Relevance
“…Indeed, some investigators have reported elevated basal or stimulated levels of plasma luteinizing hormone when serum testosterone levels are low in cohorts of subjects with SCI (3941). However, as in our report herein, other investigators have reported in persons with SCI that the basal levels of plasma luteinizing hormone were not elevated despite the presence of depressed serum testosterone concentrations (12, 42, 43). As previously discussed, a subset of our hypogonadal subjects with SCI did not have adequate responses to one or more doses of hCG.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, some investigators have reported elevated basal or stimulated levels of plasma luteinizing hormone when serum testosterone levels are low in cohorts of subjects with SCI (3941). However, as in our report herein, other investigators have reported in persons with SCI that the basal levels of plasma luteinizing hormone were not elevated despite the presence of depressed serum testosterone concentrations (12, 42, 43). As previously discussed, a subset of our hypogonadal subjects with SCI did not have adequate responses to one or more doses of hCG.…”
Section: Discussionsupporting
confidence: 64%
“…27 Since CA has been implicated in the acute-exercise in duced elevations in T then one might expect an exaggerated T response in SCI athletes using boosting since T levels at rest are normal in this population. [18][19][20][21][22][23][24][25] In addition AD is associated with elevated cortisol (C) levels27 which have been suggested as a direct inhibitor of testosterone produc tion.28,29 The SCI athlete thus provides a model to examine the effects of CA and C on the exercise induced increment in testo sterone levels. To date the T response in SCI to acute exercise has not been docu mented.…”
Section: Wheeler 1mentioning
confidence: 99%
“…334 Ten years after spinal cord injury, testicular volumes were not different from those of healthy controls, but even in medically stable men, spinal cord injury was associated with lower testosterone and LH levels than those of healthy men, 335 with a greater prevalence of low-normal testosterone levels than reported in population-based cohorts. 334 Ten years after spinal cord injury, testicular volumes were not different from those of healthy controls, but even in medically stable men, spinal cord injury was associated with lower testosterone and LH levels than those of healthy men, 335 with a greater prevalence of low-normal testosterone levels than reported in population-based cohorts.…”
Section: Neurologic Disordersmentioning
confidence: 85%